2016
DOI: 10.3329/bjp.v11i2.25031
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel antimicrobial peptide AWRK6

Abstract: We have previously identified an antimicrobial peptide called dybowskin2-CDYa (Dy2) in the cutaneous secretion from the Chinese frog Rana dybowskii. In this study, we used Dy2 as a template to prepare some novel peptides with improved stability and hydrophobicity. The antimicrobial activities exerted by these peptides against Gram positive and Gram negative bacteria were evaluated by MIC and CFU assays under physiological conditions. One peptide, AWRK6, was 2-4 fold more potent than Dy2, and was toxic to most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
(31 reference statements)
0
12
0
Order By: Relevance
“…This peptide was used to generate the cationic homologue, AWRK6, by the substitution of lysine residues for each of the six arginines possessed by Dy2, as well as the substitution of tryptophan residue for alanine at position 2 of Dy2 (Table 2). In the case of both peptides, alkaline pH promoted increased levels of α-helical structure in the presence of membranes that correlated with enhanced antibacterial activity 265 . Previous studies have shown that pH induced increases in the α-helicity of AMPs can enhance their amphiphilicity and / or hydrophobicity, thereby facilitating higher levels of membranolytic action 37 .…”
Section: Amps From Amphibiansmentioning
confidence: 93%
“…This peptide was used to generate the cationic homologue, AWRK6, by the substitution of lysine residues for each of the six arginines possessed by Dy2, as well as the substitution of tryptophan residue for alanine at position 2 of Dy2 (Table 2). In the case of both peptides, alkaline pH promoted increased levels of α-helical structure in the presence of membranes that correlated with enhanced antibacterial activity 265 . Previous studies have shown that pH induced increases in the α-helicity of AMPs can enhance their amphiphilicity and / or hydrophobicity, thereby facilitating higher levels of membranolytic action 37 .…”
Section: Amps From Amphibiansmentioning
confidence: 93%
“…Replacement of the Arg residues originally present in dybowskin-2CDYa with Lys residues resulted in higher affinity to anionic liposomes than to zwitterionic ones. Studies of antimicrobial activity indicated that AWRK6 was more active against Gram-positive than Gram-negative bacteria, and was 2–4-fold more potent compared to dybowskin-2CDYa, being found to be at the level of 4–8 μg/mL against S. aureus and 32 μg/mL against E. coli [ 13 ].…”
Section: De Novo Designed Antimicrobial Immunomodulatory Peptidesmentioning
confidence: 99%
“…Amphibian skin secretions are a rich source of bioactive peptides [ 1 , 5 ]. In our previous study, a series of novel peptides were discovered in frog ( Rana dybowskii ) skin, and dybowskin-2CDYa was later modified to improve the stability, acquiring a novel peptide, namely AWRK6 [ 6 , 7 ]. AWRK6 presented antibacterial and lipopolysaccharide-neutralizing activities, and it has been discovered that AWRK6 regulates glycolipid metabolism to improve type 2 diabetes mellitus and metabolic associated fatty liver disease (MAFLD) [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%